Financial Risks in Chinese Enterprises' Cross-border Mergers and Acquisitions - Zhang, Yu (2011)
In early 1980s, China started its economic reform after thirty years isolation from world economy. Along its opening to outside world to encourage international trade and attract inbound foreign direct investment (FDI) to China, its own enterprises, both state-owned and private-owned also started to embrace the international market by marketing their product globally and expanding its business operations to new territories through outward FDI, mainly in forms of cross-border mergers and acquisitions (M&As), and joint-venture with foreign partners. In this paper, we discuss the main financial risks that Chinese enterprises encountered in their cross-border M&A deals and the causes of such risks in context of internationalization of companies from emerging economy (EE). Through literature reviews, secondary data analysis and case studies, we have identified the major financial risks in M&A as valuation/pricing risk, financing risk and risk from payment structure. These risks have their unique/specific reflection when faced by Chinese enterprises in their cross-border M&As. The research shows that for Chinese companies‟ cross-border M&As, the valuation risk was mainly caused by information asymmetry, especially lack of labour law and industrial relation knowledge of host countries, which led to underestimated labour-related costs in post acquisition business integration. The pricing risk is a result of valuation risk and competition for deals.Interestingly, though many M&A practitioner‟s manuals indicated the primary financial risk in M&A is the risk arsing from leverage financing for acquisition, in reality, leverage financing risk itself is insignificant in Chinese companies‟ cross-border M&A deals. However, currency choice of leverage financing is a factor that acquiring company cannot ignore in its assessment on overall financial risks of an M&A deal. In the context of internationalisation of EE MNCs, these identified financial risks were rooted in the special CSAs based growing model of Chinese MNCs. In recent years, the major force of Chinese companies overseas M&A deals are large state-owned enterprises targeting on tangible assets especially natural resources. This trend, on one side, is the reflection of China‟s national energy security strategy in business arena, on another side; it is also the result of several high-profile unsuccessful M&A deals conducted by Chinese companies in IT, manufacturing sectors in the early Years of first decade of 21st century.